Draft genome sequence of extended-spectrum β-lactamase-producing klebsiella pneumoniae isolated from a patient in Lebanon - Tokajian, Sima (2014)
We present the draft genome sequence of extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae isolated from a stool sample collected from a patient admitted for a gastrointestinal procedure. The draft genome sequence consists of 86 contigs, including a combined 5,632,663 bases with 57% G+C content.